Чат-бот як інструмент автоматизації комунікації з клієнтами фотостудії - Мельникова, Анастасія; Кравець, Руслан (Видавництво Львівської політехніки, 2025)
This article examines the implementation of chatbots as tools for automating client communication in photography studios. The study analyzes the effectiveness of chatbots in handling routine client inquiries, appointment scheduling, and providing information about services. A model of a chatbot for photography studios based on natural language processing is presented, along with implementation challenges and potential benefits for business optimization.
Keywords: чат-бот; автоматизація комунікації; фотостудія; обслуговування клієнтів; штучний інтелект; бізнес-процеси; цифрова трансформація